Studi bibliometrik tentang trend penelitian restrukturisasi organisasi riset menggunakan VOSviewer - Nur Aulia; Eko Ruddy Cahyadi; Bagus Sartono (Perpustakaan Universitas Gadjah Mada, 2023)
Introduction. The development of organizational restructuring has growth rapidly. The research aims to see and find out the development of research trends on organizational restructuring. It also aims to see opportunities for future research on organizational restructuring, particularlyin public research organizations.Data Collection Methods. The paper used a quantitative bibliometric analysis with the Scopus database for the last 10 years from 2013 to 2022. Data Analysis. Bibliometric data analysis uses co-occurrence to visualize keywords, networks, density, and overlays. The visualization results are presented using VOSviewer software with a comprehensive narrative method. Results and Discussion. The finding showed that the organizational restructuring research has been dominated by the private sector. Meanwhile however, in the public sector, it showed that the health sector played a significant role. The United States became the country that has discussed the topic of organizational restructuring most extensively. In addition, based on keywords, there were four visualization clusters: human, organizational change, organizational culture, and health care organization. Conclusion. Opportunities show for organizational restructuring research at public research institutions. Other approaches need to be explored instead of using bibliometric analysis.